Prevalence of Toxoplasmosis Among Women of Reproductive Age in Mukalla City, Yemen: A Comparative Study of Rapid Cassette Test and Cobas e411 - Hassan Pyar; Anwar Salem Al-Hussein; Amani A. Bin Nasser; Ahmed Bawazir; Noura Bawazir; Sarah O. Alsawmhi (Biology, Medicine, & Natural Product Chemistry, 2026)
Toxoplasma gondii is an obligate intracellular parasite that affects a wide range of mammals, including humans, which serve as intermediate hosts. This cross-sectional study enrolled 85 women during its initial stage. The second stage was the laboratory investigation that included the Cassette and Cobas e 411 tests. The overall seroprevalence of T. gondii in the study area was 58.82%. The seropositivity of anti-Toxoplasma IgG (58.82%) was higher than that of anti-toxoplasma IgM (1.18%) by the Cobas test, whereas IgG-positive and IgM-positive cases accounted for 55.29% and 4.71%, respectively, by the Cassette test. This suggests that T. gondii IgG antibodies in women are a reflection of chronic or past infection, while IgM reflects recent and acute T. gondii infection. The highest seropositive rate (70%) was recorded in the age group 33-38. The low sero-positive rate (54.55%) was recorded in the age group 21-26. The present study revealed that 50 % statistic in the abortion results. The results show that women with one previous abortion had a high (53.85%) seroprevalence of T. gondii antibodies. Higher sero-positive toxoplasmosis was recorded among women from Al-Deas zones (68.75%), revealing that the rate of infection among low-level women was high (75%). The ownership of animals in relation to the infection was studied. The highest seropositive rate was recorded among women who kept sheep and goats (71.43%), compared to 50% for cat owners, showing a statistically significant difference (P < 0.001). In conclusion, toxoplasmosis is a major public health issue among the studied population in Yemen. The Cobas e411 system offers superior sensitivity over the cassette method for antibody detection. Community-wide educational programs emphasizing hygienic animal handling are recommended, alongside the adoption of highly accurate testing protocols to improve diagnostic accuracy.